Bridging tradition and innovation: a systematic review on integrating communication skills in hadith studies and technical education for the 21st Century learner in TVET institutions - Ahmad, Khalilullah Amin; Rashid Ali, Farrah Diebaa; Abd Hamid, Mohd Azrul Azlen (RSIS International, 2025)
This study undertakes a systematic literature review on the intersection of Hadith pedagogy, communication skills and technical education under the theme “Bridging Tradition and Innovation: Integrating Communication Skills in Hadith Studies and Technical Education”. Despite the increasing relevance of communication competence in modern education, limited scholarship has examined its integration within Islamic studies particularly in Hadith pedagogy alongside technical and professional domains. Addressing this gap, the review applied an advanced search strategy across Scopus and Web of Science databases using the keywords “Hadith Pedagogy,” “Communication Skills,” “Technical Education,” “Curriculum Integration” and “Educational Innovation.” Following the PRISMA framework, 96 records were initially identified and rigorously screened; exclusions were made based on language, publication type, disciplinary scope, and accessibility criteria. A final sample of 32 peer-reviewed articles was retained for qualitative synthesis. Thematic analysis of these studies revealed three overarching themes: (1) pedagogical approaches and curriculum innovation in religious education, which highlight the potential of problem-based, project-based and interdisciplinary models for enriching Hadith studies; (2) religion, intercultural dialogue and societal integration, which underscore the role of communication skills in fostering tolerance, moderation and mutual understanding across diverse educational contexts; and (3) digitalization, collaborative learning and educational technology, which demonstrate how digital platforms, social media, and collaborative pedagogies transform both the teaching of Hadith and its connection to technical and professional skill development. Collectively, these findings illustrate how bridging traditional Islamic scholarship with innovative communication-oriented pedagogies can enhance the relevance of Hadith education in contemporary settings. The study concludes that integrating communication skills into Hadith pedagogy and technical education offers not only pedagogical advancement but also societal value by nurturing critical, adaptive and interculturally competent learners.